Composição corporal e exigências nutricionais de energia para novilhos da raça sindi - Cambuí, Gabriela Brito (2015)
The objective was to determine body composition and nutritional requirements of energy and protein in steers of Sindi. The experiment was conducted at the Federal University of Viçosa (UFV), we used the comparative slaughter technique using 40 non-castrated animals with a mean age of 21 ± 1.5 months and average body weight of 296.65 ± 21.33 kg and four food restriction levels (0, 15, 30 and 45%) in a completely randomized design. Of the 40 animals, 8 were slaughtered at the beginning of the experiment, constituted the reference group. The 32 remaining animals were confined for 74 days, soon after all animals 8 were slaughtered of each time to determine the body composition by chemical analysis of tissues. We evaluated two methods (Direct and Indirect) for the determination of net and metabolizable requirements of energy for maintenance (NEm, MEm), protein for maintenance (NPm MPm); and to also energy gain (RE) and protein (RP). The requirements of NEm and MEm were respectively 42,38 and 52,46 kcal/EBW0,75/day, and the models obtained for RE and RP were RE = 0.0490 * EBW0,75 * EBG0,3730 and RP = 183,172 + 112,668 ADG - 26,818 RE. The requirements of NPm and MPm obtained for Sindi steers were 1.23 and 3.24 g/EBW0,75/day, respectively. The use efficiency of metabolizable energy for maintenance and gain were 78,88 and 45,37% respectively and metabolizable protein for gain was 45,96%.